STRATEGI PENGEMBANGAN PT SAYURAN SIAP SAJI DI DESA SUKAMANAH KECAMATAN MEGAMENDUNG KABUPATEN BOGOR - Tiara Kartika Sari; Wuryaningsih Dwi Sayekti; Achdiansyah Soelaiman (Lampung University, 2017)
The purpose of this research are to analyze the internal and external environment, the customers attitude, and the development strategy of agribusiness in PT Sayuran Siap Saji. This research uses a case study method in PT Sayuran Siap Saji. Respondents of this research are employee and customers of PT Sayuran Siap Saji, and Department of Agriculture and Forestry Bogor District and Department of Cooperative, UKM, Industry, and Trade Bogor District. Data analysis method that used in this research are descriptive qualitative analysis (SWOT) and descriptive quantitative (analysis of customer attitudes). The result of this research shows that: (1) the main strength of PT Sayuran Siap Saji is a good product quality, while the main weakness is the lack of promotion. The main opportunity of PT Sayuran Siap Saji is increasing number of restaurants that require fresh cut vegetable products, while the main threat is the customers switch to another company, (2) the biggest of customers attitude value to the attributes PT Sayuran Siap Saji is an on time delivery attribute, (3) the main priority strategy of PT Sayuran Siap Saji is manage a better management functions to affect the performance of the company, technology development, and customers loyalty. In addition, maintaining product quality in order to remain certified HACCP by using good raw materials, appropriate technology, the specialization of labor, and do a promotion activities. Keywords: customers attitude, development strategy, fresh cut vegetable